Concept of Agni and Aama in Brihattrayi -A Review - Singh, Naval; Dabhi, Amisha Labhubhai; Gupta, Nisha (International Research Journal of Ayurveda & Yoga, 2023)
Primary Prayojana of Ayurveda "Swasthasya swasthaya rakshanam aturasya vikara prashamanam cha ". Concept of Agni is a basic concept of Ayurveda classical texts. This concept has its own importance for maintenance of the health of a healthy person as well as for curing the various diseases. One should always careful for normal status of the all Agni’sfor maintenance of health. In the disease state vitiated Doṣha, Dhatu or Mala can be corrected with treatment of respective Agni. Agni is believed to be the agency for any kind of transformation. These may be bio chemical or bio physical or any other type of bio transformations. Due to these constant transformation procedures, body grows, develops and lastly destroys too. Diseased state of the body is also some pathological changes either functional or structural. Thus, the principle of Agni becomes vital as either the healthy or the diseased state can only be understood with understanding of changes and according to Ayurvedic principles, all these procedures cannot be possible without Agni. In Bruhattryi, all information related to Agni & 13 types of Agni’s according to their locations and functions of transformation at different levels of digestion and metabolism are described. With the help of its own Agni, each body substance gets nourished and can perform its normal functions. Aama is a toxic, disease causing substance that forms as a result of impaired Agni .